Saliva as a diagnostic tool to measure polycyclic aromatic hydrocarbon exposure in dental patients exposed to intimate partner violence (IPV) - Aramandla Ramesh; Leslie R. Halpern; Janet H. Southerland; Samuel E. Adunyah; Pandu R. Gangula (Biomedical Journal, 2023)
Background: Social habits such as tobacco use, alcohol consumption, and chemically contaminated diet contribute to poor oral health. Intimate Partner Violence (IPV) is a global public health epidemic which can exacerbate the prevalence of health conditions affecting a victim's lifespan. This study investigates using saliva as a biomarker for detecting levels of benzo(a)pyrene [B(a)P]; a toxicant present in cigarette smoke and barbecued meat in a population of IPV + female patients. Methods: A cross-sectional IRB-approved study utilized 63 female participants (37 African Americans [AA], and 26 non-African Americans [NAA]), who provided consent for the study. Participants submitted samples of saliva, as well as questionnaires about demographics, health history, and a well-validated (IPV) screen. Results: The prevalence of IPV was greater in AA compared to NAA. While the concentrations of PAHs/B(a)P detected in saliva of IPV samples in NAA were generally within the range of B(a)P reported for saliva from elsewhere, the concentrations were high in some IPV positive samples. Among the B(a)P metabolites, the concentrations of B(a)P 7,8-diol, B(a)P 3,6- and 6,12-dione metabolites were greater than the other metabolite in both AA and non-AA groups who were positive. Conclusion: Our study supports the use of saliva as a potential “diagnostic rheostat” to identify toxicants that may exacerbate/precipitate systemic disease in female victims of IPV. In addition, our study is the first to report that IPV may precipitate the accumulation of B(a)P in oral cavity that can alter inflammatory cascades and increase risk of poor health outcomes in this population of patients.